THE DISCUSSION OF QIRA’AT TURJUMAN AL-MUSTAFID EXEGESIS BOOK BY SHEIKH ABDUL RAUF SINGKEL - Khairunnas Jamal; Wan Nasyaruddin Wan Abdullah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2016)
Muslims got mercy upon the provision of differences in reading al-Qur`an. The differences have made significant influence on the interpretation of the Holy Book. The commentators of al-Qur`an adopted the qira’at differences as an integral part of their interpretation. For example, Ibn Jarir al-Tabari who wrote Tafsir al-Tabari and Abdul Rauf Singkel who wrote Tafsir Turjuman al-Mustafid. Abdul Rauf Singkel was a famous Qur’anic exegesis scholar in the Indonesia Archipelago whose work became the main reference of Muslims alongside the archipelago. In interpreting the verses of al-Qur`an, Abdul Rauf put qira’at distinction as one of his focuses of interpretation. In his work, Shaikh Abdul Rauf cited only three of the available seven qira’ats that he considered mutawatir and valid. Among those three qira’ats is qira’at Imam Nafi’, qira’at Imam Abu Amr and qira’at Imam Hafash. This study has shown despite differences in the implication of the qira’ats, there also the differences in meaning and understanding. Shaikh Abdul Rauf merely provided information about the difference in readings rather than showing a difference of meaning contained in each of the differences